Analisis Sistem Pengendalian Internal Gaji dan Upah Pada Pengadilan Tata Usaha Negara Palembang - Akhmad Khudri; Deti Marlina (Jurnal Ilmiah Matrik, 2023)
Abstract : The Palembang State Administrative Court (PTUN) is one of the mainstays of regulatory conditions in Indonesia in its ability to complement the power of law, especially to decide issues that occur in state organizations and organizations or government businesses within the scope of South Sumatra, the Bangka Belitung Islands Region. The Palembang State Administrative Count in managing data is quite good but the way when it is going to follow transactions into an application, especially regarding the management of employee salary and wage data still looks quite complicated and difficult to operate except by the person who holds the application system. Therefore the author makes an application that is easier to operate, so that it can help when inputting salary transactions. This study uses the waterfall method and the modeling language UML (unified Modeling Language), xampp, PHP Rad classic and database.